Development, optimization, and evaluation of PEGylated brucine-loaded PLGA nanoparticles - Elsewedy, Heba S. (Drug Deliv, 2020)
The application of nanotechnology to drug delivery systems for cancer therapy has progressively received great attention. The most heavily investigated approach is the development of nanoparticles (NPs) utilizing biodegradable and biocompatible polymers such as poly (lactic-co-glycolic acid) (PLGA). These NPs could be further improved by surface modification utilizing a hydrophilic biodegradable polymer such as polyethylene glycol (PEG) to achieve passive targeting. Modified NPs can deliver drugs such as brucine (BRU), which has shown its potential in cancer therapy. The objective of the current investigation was to develop and evaluate the passive targeting of long-circulating PLGA NPs loaded with BRU. NPs were characterized in terms of drug-excipient compatibility studies, including FTIR and DSC; physicochemical evaluations including particle size, zeta potential, morphological evaluation, entrapment efficiency and percentage yield; total serum protein adsorbed onto NP surfaces; and in vitro release of the loaded drug. Factorial design was employed to attain optimal PLGA-loaded NPs. Finally, the in vivo anti-tumor activity of BRU-loaded PLGA NPs was evaluated in tumor-bearing mice. The NPs obtained had smooth surfaces with particle sizes ranged from 94 ± 3.05 to 253 ± 8.7 nm with slightly positive surface charge ranged from 1.09 ± 0.15 to 3.71 ± 0.44 mV. Entrapment of BRU ranged between 37.5 ± 1.8% and 77 ± 1.3% with yields not less than 70.8%. Total protein adsorbed was less than 25.5 µg total protein/1 mg NP. In vitro drug release was less than 99.1% at 168 h. Finally, significant reductions in tumor growth rate and mortality rate were observed for PEG PLGA NP formulations compared to both BRU solution and naked NPs.